Inducción al desove en hembras del pargo mancha, Lutjanus guttatus (Steindachner, 1869) (ING) - Valverde Chavarría, Silvia (1998)
The effect of carp pituitary extract (EPC) was studied in six mature females of the spotted snapper, Lutjanus guttatus, caught by bottom long lines by artesanal fishermen in the Nicoya gulf. The female weights were between 1.7 and 2.0 kg. Three females were injected with 800 UI EPC/Kg body weight, the rest were used as a control group. The frequency distribution of oocyte diameters and their maturity status were assessed immediatedly before and 24 h and 48 h after the application of the hormonal treatment. Two of the injected females spawned once, 24 hours after the application of the hormonal stimulus, expelling 115,500-125,500 eggs, with a mean diameter of 0.724 mm.